Republic of Tajikistan : Poverty Reduction Strategy Paper: Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
The National Development Strategy of the Republic of Tajikistan mainly complements future renewals and ensures implementation of the development process of the country. The fields of activity of the world community outlined in the Millennium Declaration comply with the national goals and priorities of Tajikistan. In accordance with the National Development Strategy of the Republic of Tajikistan and Poverty Reduction Strategy for the period of 2010-12, priority areas for further development of complex spheres in separate sectors are unified, which basically covers public administration reform and private sector development.